Subfunctionalization of duplicate MYB genes in Solanum commersonii generated the cold‐induced ScAN2 and the anthocyanin regulator ScAN1. (2nd June 2017) - D'Amelia, Vincenzo; Aversano, Riccardo; Ruggiero, Alessandra; Batelli, Giorgia; Appelhagen, Ingo; Dinacci, Claudio; Hill, Lionel; Martin, Cathie; Carputo, Domenico
Abstract: Wild potato species are useful sources of allelic diversity and loci lacking in the cultivated potato. In these species, the presence of anthocyanins in leaves has been associated with a greater tolerance to cold stress. However, the molecular mechanisms that allow potatoes to withstand cold exposure remain unclear. Here, we show that the expression of AN2, a MYB transcription factor, is induced by low temperatures in wild, cold‐tolerant Solanum commersonii, and not in susceptible Solanum tuberosum varieties. We found that AN2 is a paralog of the potato anthocyanin regulator AN1, showing similar interaction ability with basic helix–loop–helix (bHLH) co‐partners. Their sequence diversity resulted in a different capacity to promote accumulation of phenolics when tested in tobacco. Indeed, functional studies demonstrated that AN2 is less able to induce anthocyanins than AN1, but nevertheless it has a strong ability to induce accumulation of hydroxycinnamic acid derivatives. We propose that the duplication of R2R3 MYB genes resulted in subsequent subfunctionalization, where AN1 specialized in anthocyanin production and AN2 conserved the ability to respond to cold stress, inducing mainly the synthesis of hydroxycinnamic acid derivatives. These results contribute to understanding the evolutionary significance of gene duplication on phenolic compound regulation. Abstract : This paper functionally analyses the differences of two potato anthocyanin paralog MYB genes ScAN2 and ScAN1 and the response of the former to low temperatures. These are the major relevant aspects it underlines: (1) the historical evolution of ScAN2 and ScAN1, where ScAN2 retains the ability to be cold induced only in tolerant Solanum commersonii and not in sensitive Solanum tuberosum ; (2) the different functionality of ScAN2 and its paralog ScAN1 to activate anthocyanins in a heterologous system; (3) the capacity of ScAN2 to activate hydroxycinnamic acid derivatives, important precursors of lignin and suberin production, and known compounds to face environmental stresses.